Study the Adsorption of Basic Violet 10 Dye onto Olive Kernels Powder as Adsorbent in Aqueous Solution - AL-Mammar, Dunya Edan; Mohammed, Rawaa Abbas (Iraqi Journal of Science, 2025)
The study evaluates the potential of powdered olive kernels as a natural adsorbent for extracting basic violet 10 dye from contaminated water using adsorption methods. The adsorbent material was characterized using Fourier transform infrared spectroscopy (FTIR) and atomic force microscopy (AFM). The impact of various operating variables namely, dosage of olive kernels powder, adsorption period, starting BV10 dye concentration, temperature and pH were investigated. The experimental data obtained from the equilibrium adsorption studies fitted better with the Freundlich adsorption isotherm model compared to the Langmuir isotherm model. Kinetics analysis for adsorption process revealed that the pseudo-second-order model (PSOM) was more appropriate to describe the sorption process constructed to pseudo-first-order (PFOM). Thermodynamics data for the adsorption of BV10 dye onto kernels powder surface display that this process is spontaneous and exothermic in nature.